Community seed banks as seed producers: Cases from India, Nepal, Uganda and Zimbabwe - Vernooy, Ronnie; Jai, Rana; Ahlawat, Sudhir Pal; Malik, S.K.; Mbozie, Hilton; Mugisha, Joy; Nyabasha, Sylvia; Otieno, Gloria Atieno; Patil, Sanjay; Roy, Somnath; Shrestha, Pitambar; Tiwari, Shailendra; et al. (CGIAR Research Program on Grain Legumes and Dryland Cereals, 2020)
Community-based seed producers are a relatively under-researched and under-documented category of seed producers, but have the potential to cater to the diverse seed needs and interests of smallholder farmers. This working paper presents a number of such community-seed producers, with a focus on community seed banks. The case studies from India, Nepal, Uganda and Zimbabwe point to the viability of community seed banks as seed producers and distributors, but becoming successful is not easy and depends on several factors, including initial technical guidance and support, sufficient time, adherence to a seed value chain perspective and the development of a sound business plan from the very start.